Healthy life styles and perceived health status in the general population of a Northern Italian health district: a cross-sectional study (Italian Journal of Public Health, 2010)
Background: Evidence should drive public health initiatives to better address the most important healthissues. Chronic diseases represent the main burden of healthcare expenditure in Western countries andare determined by risk factors related to behaviour. Population-based surveys should lead to well informeddecision making in this field.Methods: A cross-sectional survey was carried out among the general population aged between 18 and69 in the district of Monza-Brianza in Northern Italy through phone interviews. A validated questionnaireinvestigating health-related lifestyles and behaviours was used. The questionnaire was divided into thefollowing parts: general health status, physical activity, smoking habit, nutrition, alcohol consumption,driving safety, cardiovascular risk, cancer screening, mental health, domestic safety and socio-economicstatus.Results: In total, 308 interviews were carried out (response rate=76%). Almost 40% reported a body massindex >25, 64.9% had high school or university degrees, 60.4% worked full-time, 26.2% were assessedas physically inactive, and 13.3% were on a weight –loss diet. In addition, 19.7% had an “at risk” alcoholconsumption , especially among younger age groups. Symptoms of depression were identified in 4.9% of thestudy subjects, particularly in women.Conclusions: Age, body mass index, education, and occupation were significantly associated with thelikelihood of reporting poor health status. Young subjects were more likely to be smokers and drinkers atrisk. Psychological health and appropriate prescription of anti-cholesterol and anti-hypertensive drugs areareas deserving further investigations. Nutrition, physical activity, driving safety and youth health, especiallyconcerning drinking habits, are areas where initiatives should be undertaken
Keywords: health survey; life style; motor activity; nutrition; smoking; alcohol drinking